Analysis Of Student Satisfaction in Accounting Study Program Using Higher Education Image Moderation Post Pandemic Covid-19 - Tandry Whittleliang Hakki; Merna Surjadi; Cinthia Andriani; Michelle Natalia (Dinasti International Journal of Education Management And Social Science, 2023)
The purpose of this study was to examine (1) Student Service Quality has a significant and positive effect on Student Satisfaction. (2) Academic Service Quality has a significant and positive effect on Student Satisfaction. (3) Institutional Culture has a significant and positive effect on Student Satisfaction (4) Institutional Image strengthens the influence between Student Service Quality on Student Satisfaction. (5) Institutional Image strengthens the influence between Academic Service Quality on Student Satisfaction. (6) Institutional Image strengthens the influence between Institutional Culture on Student Satisfaction. by using multiple regression. Based on the results of this study indicate that Student Service Quality has a significant and positive effect on Student Satisfaction but Academic Service Quality and Institutional culture has a not significant on Student Satisfaction. Then, Institutional Image strengthens the influence between Student Service Quality on Student Satisfaction but Institutional image and Institutional Image not strengthens the influence of Academic Service Quality on Student Satisfaction.